MELACAK BIAS GENDER DALAM PENAFSIRAN KEMENTERIAN AGAMA RI PADA AL-QUR’AN SURAH AN-NISA DAN AL-BAQARAH - Nur Laili Nabilah Nazahah Najiyah; Abdul Hamid; Asa Ade Muliana (Jurnal Harkat : Media Komunikasi Gender, 2022)
Abstract. Gender bias is an injustice in the division of positions and roles between men and women. Factors that cause bias are the values and norms of society which tend to limit women's space for movement. These understandings of gender bias often get support from patriarchal readings of the Qur'an. Therefore, this research specifically presents a gender-biased form of interpretation of Qur'anic verses in the Interpretation of the Ministry of Religion of the Republic of Indonesia. These verses are QS. an-Nisa: 34 and QS. al-Baqarah: 282. There are two formulations of the problem that are discussed in this study, namely first, what is the nature of the concept of gender bias; and second, the form of gender bias in the interpretation of the book of commentary "Al-Qur`an and its Interpretations" written by the Commentary Team of the Indonesian Ministry of Religion. Analysis of the study is carried out with several steps of activities simultaneously, namely condensation and presentation of data, as well as verification (conclusion). In addition, explanatory analysis is needed to find out and at the same time clarify in depth the content/meaning contained in the QS. an-Nisa: 34 and QS. al-Baqarah: 282. The result is that a biased understanding often gets support from a patriarchal reading of the Koran. In his interpretation of QS. al-Nisa': 34 and QS. al-Baqarah: 282, there is an interpretation of these verses where there is a hierarchical (position) which seems to indicate the wife's position is under (control) of the husband and reflects an attitude of subordination. Abstrak. Bias gender merupakan suatu ketidakadilan dalam pembagian posisi dan peran antara laki-laki dan perempuan. Faktor penyebab adanya bias adalah nilai dan norma masyarakat yang cenderung membatasi ruang gerak perempuan Pemahaman-pemahaman bias gender ini seringkali mendapat dukungan dari pembacaan al-Qur`an secara patriarkis. Karenanya, penelitian ini secara khusus menyajikan bentuk penafsiran ayat-ayat al-Qur`an yang bias gender dalam Tafsir Kementrian Agama RI. Ayat-ayat tersebut yaitu QS. an-Nisa: 34 dan QS. al-Baqarah: 282. Ada dua rumusan masalah yang menjadi bahasan dalam penelitian ini, yaitu pertama, bagaimana hakikat konsep bias gender; dan kedua, bentuk bias gender dalam penafsiran kitab tafsir “Al-Qur`an dan Tafsirnya” yang ditulis oleh Tim Mufasir Kementrian Agama RI. Analisis kajian dilakukan dengan beberapa langkah kegiatan secara bersamaan, yakni kondensasi dan penyajian data, serta verifikasi (kesimpulan). Selain itu, analisis eksplanatoris dibutuhkan untuk mengetahui sekaligus memperjelas secara mendalam kandungan/makna yang terkandung dalam QS. an-Nisa: 34 dan QS. al-Baqarah: 282. Hasilnya, bahwa pemahaman yang bias seringkali mendapat dukungan dari pembacaan al-Qur`an secara patriarkis. Dalam penafsirannya pada QS. al-Nisa’: 34 dan QS. al-Baqarah: 282, terdapat sebuah tafsir atas ayat-ayat tersebut terdapat sebuah hierarkis (kedudukan) yang seakan menunjukkan posisi istri berada di bawah (kendali) suami dan mencerminkan adanya sikap subordinasi.